Syndemic Risk Classes and Substance Use Problems among Adults in High-Risk Urban Areas: A Latent Class Analysis - Cleland, Charles M.; Lanza, Stephanie T.; Vasilenko, Sara A.; Gwadz, Marya (Frontiers in Public Health, 2017)
Substance use problems tend to co-occur with risk factors that are especially prevalent in urban communities with high rates of poverty. The present study draws on syndemics theory to understand profiles of risk and resilience and their associations with substance use problems in a population at-risk for adverse outcomes. African American/Black and Hispanic heterosexual adults (N=2853) were recruited by respondent-driven sampling from an urban area with elevated poverty rates, and completed a structured assessment battery covering sociodemographics, syndemic factors (that is, multiple, co-occurring risk factors), and substance use. More than one third of participants (36%) met criteria for either an alcohol or a drug problem in the past year. Latent class analysis identified profiles of risk and resilience, separately for women and men, which were associated with the probability of a substance use problem. Almost a third of women (27%) and 38% of men had lower-risk profiles – patterns of resilience not apparent in other types of analyses. Profiles with more risk and fewer resilience factors were associated with an increased probability of substance use problems, but profiles with fewer risk and more resilience factors had rates of substance use problems that were very similar to the general adult population. Relative to the lowest-risk profile, profiles with the most risk and fewest resilience factors were associated with increased odds of a substance use problem for both women (adjusted odds ratio [aOR] = 8.50; 95% CI: 3.85 – 18.74) and men (aOR = 11.68; 95% CI: 6.91 – 19.74). Addressing syndemic factors in substance use treatment and prevention may yield improved outcomes.